Examination of the Patient and Hospitalization Characteristics of 30-Day SCD Readmissions. Issue 9 (September 2016) - Carroll, C. Patrick; Haywood, Carlton; Lanzkron, Sophie M.
Abstract : Objectives: Sickle cell disease (SCD) is associated with a high level of emergency department and hospital utilization, as well as a high rate of hospital readmissions. At Johns Hopkins Hospital, as at other institutions, SCD accounts for a large proportion of readmissions. Our study examined patient and hospitalization factors involved in readmissions at Johns Hopkins Hospital. Methods: Patients at the Johns Hopkins Sickle Cell Center for Adults with a readmission in fiscal year 2011 were compared with an age- and sex-matched sample of clinic patients for comorbidities, complications, and prior utilization. Hospitalizations that were followed by readmissions were compared with those that were not as to admitting service, length of stay, and average daily opioid dose. Results: Patients with readmissions had more complications and comorbidities and much higher prior utilization than typical clinic patients, whereas hospitalizations that were followed by readmissions had a longer length of stay but similar opioid doses. Conclusions: For patients with SCD with a high volume of hospital use, readmissions may be a natural consequence of a high-admission frequency associated with greater disease severity and higher comorbidity. Abstract : Thirty-day hospital readmissions have been put forward as a measure of the quality of hospital care. Patients with sickle cell disease (SCD) have high hospital readmission rates and high rates of hospital utilization in general, and they account for a disproportionate amount of hospital readmissions. In this study, patient and admission characteristics of all readmissions for SCD at Johns Hopkins Hospital for 1 year were compared with SCD clinic patients with no readmissions.